Chrysoeriol ameliorates hyperglycemia by regulating the carbohydrate metabolic enzymes in streptozotocin-induced diabetic rats - Baskaran Krishnan; Abirami Ramu Ganesan; Ravindran Balasubramani; Dinh Duc Nguyen; Soon Woong Chang; Shaoyun Wang; Jianbo Xiao; Balamuralikrishnan Balasubramanian (Food Science and Human Wellness)
The present study aimed to evaluate the effects of chrysoeriol from Cardiospermum halicacabum in streptozotocin induced Wistar rats. Thirty rats were categorized as control, diabetic control supplemented with 0, 20 mg/kg chrysoeriol and 600 μg/kg BW of glibenclamide for 45-day trial period. Our results indicated that the inclusion of chrysoeriol (20 mg/kg), showed a significant reduction in plasma glucose, hemoglobin and glycosylated hemoglobin level with a rising of plasma insulin sensitivity. Further, downregulated enzymes including glucose 6-phosphatase, fructose 1,6-bisphosphatase, and glycogen phosphorylase as well upregulated enzymes such as hexokinase, glucose-6-phosphate dehydrogenase, pyruvate kinase, and hepatic glycogen content. There was a diminish action found in liver glycogen synthase of tested rat with a rise in gamma-glutamyl transpeptidase, towards normal levels upon treatment with chrysoeriol. The histopathological study confirmed that renewal of the beta cells of pancreatic of chrysoeriol and glibenclamide treated rats. In addition, the molecular docking of chrysoeriol against glycolytic enzymes including hexokinase, glucose-6-phosphate dehydrogenase, pyruvate kinase, using Argus software shows chrysoeriol had greatest ligand binding energy as equivalent to glibenclamide, as a standard drug. Thus, chrysoeriol found to be non-toxic with potential regulation on glycemic control and upregulation of the carbohydrate metabolic enzymes.